Adsorption of Hg(Ii) from Aqueous Solutions on β-zeolite Theoretical-Experimental Proposal for the Surface Interaction Mechanism and the Formation of Metal Complexes - Cardenas-Jiron, G (Elsevier B.V., 2025)
A β-zeolite (Zβ) was synthesized and characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic absorption spectroscopy, nitrogen adsorption-desorption isotherms, thermogravimetric analysis (TG-DTA), and attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR). The material exhibited a Si/Al ratio of 23.3, a BET surface area of 619 m2/g, and a predominantly microporous structure. The adsorption of Hg(II) onto Zβ was rapid, reaching equilibrium within 40 min. Kinetic analysis best fitted the pseudo-second order model, indicating chemisorption on active sites, while the Freundlich isotherm suggested multilayer adsorption on heterogeneous surfaces. ATR-FTIR analysis suggests the involvement of silanol groups in the adsorption mechanism. After Hg(II) adsorption, the intensity of the hydroxyl (-OH) band at 3370 cm−1 decreased significantly, indicating interaction with the metal ions. Theoretical calculations further elucidated the adsorption mechanism, showing the formation of inner and outer sphere complexes. The inner sphere complex involved direct coordination between Hg(II) and silanol groups, while the outer sphere complex was stabilized by hydrogen bonding. The calculated reaction energies (−0.6 and −2.1 eV) supported the thermodynamic feasibility of these interactions. Density functional theory (DFT) and Ab initio molecular dynamics (AIMD) simulations revealed a significant bandgap reduction upon mercury adsorption, confirming strong electronic interactions. These findings highlight the efficiency of Zβ for Hg(II) removal, particularly at low concentrations. The combined experimental and theoretical approach provides valuable insights into the adsorption process, contributing to the design of advanced materials for heavy metal remediation. © 2025 Elsevier Inc.